Nothing Special? (Activist) Design Skills for the 21st Century - Julier, Guy . (Kepes, 2012)
Abstract This isn’t just a challenge for designers, but also for policy, design research and the representation of design through its exhibition or publication. Design is embracing new sets of skills that require extended thinking. In terms of design education, which plays a role in defining the skills necessary to designers, this dynamic is particularly challenging. In this article, rather than pursue traditional disciplinary fields – either to be found in the design profession or in its educational institutions – I move toward four conceptual frameworks that might help structure a way into considering where design skills for the 21st century might be directed. I do this in the context of increasing global resource constraints, the need to address climate change more thoughtfully and issues of social inequality and injustice that have become greater and more widespread over the past 30 years. These years have seen the growth of design in the context of the neoliberal economic and social system. Building away from this, we may see design as an active agent in forging post-neoliberal ways of living, acting and being.